Redrawing anthropology : materials, movements, lines - Ingold, Tim (Farnham, Surrey, England ; Burlington, VT : Ashgate Pub. Company, 2011)
Contents: Preface; Introduction, Tim Ingold; Materials in making, Stephanie Bunn; Practice drawing writing object, Lesley McFadyen; Networks of objects, meshworks of things, Carl Knappett; Thinking through movement: practising martial arts and writing ethnography, Rupert Cox; Learning the 'banana tree': self-modification through movement, Greg Downey; Performing precision and the limits of observation, Brenda Farnell and Robert N. Wood; The imaginative consciousness of movement: linear quality, kinaesthesia, language and life, Maxine Sheets-Johnstone; Beyond A to B, Griet Scheldeman; Drawing with our feet (and trampling the maps): walking with video as a graphic anthropology, Sarah Pink; 'Both created and discovered': the case for reverie and play in a redrawn anthropology, Amanda Ravetz; Expanded visions: rethinking anthropological research and representation through experimental film, Arnd Schneider; Index.
Includes bibliographical references and index.
boek